Kinetics, isotherm and thermodynamics of sterol adsorption on styrene-divinylbenzene anion-exchange resins - Ladadok, Chinakrit; Yamaki, Takehiro; Matsuda, Keigo; Matsumoto, Hideyuki; Na-Ranong, Duangkamol (My University, 2018)
Phytosterols can be recovered from natural resources using molecular distillation, cold crystallization, which require large energy consumption. Adsorption was considered as a feasible alternative method. In this study, kinetics, isotherm and thermodynamics of stigmasterol adsorption on styrene-divinylbenzene with two different functional groups, strong base (SB-R) and weak base (WB-R), were investigated using a model solution of stigmasterol in n-heptane. Isothermal adsorption experiments were performed in temperature range of 298-313 K and concentration range of 0.3-6.0 mg/gsol. For both SB-R and WB-R cases, kinetics of adsorption was analysed based on pseudofirst- order and pseudo-second-order models and the results revealed that pseudo-second-order model agreed with the experimental data much better than pseudo-first-order model. Analysis of isotherm data based on Langmuir, Freundlich and linear models showed that Freundlich was the best model that could predict behaviour of sterol adsorption for both SB-R and WB-R cases. In addition, thermodynamics parameters (δG, δH andδS) indicated that the sterol adsorptions on these adsorbents were spontaneous, exothermic and favourable at low temperature.
Keywords: Adsorbent; Ion-exchange resin; Phytosterols; Separation